Exposure and its working mechanisms in theatrical multi-scene model "critical dramaturgy study" (Al-Academy, 2021)
The concept of intertextuality was one of the problems that occupied the attention of critics and critics in targeting the structure of textual intertextuality between texts and their overlap in the process of producing meaning. Until intertextuality became a stable term and it can be monitored in the structure of the theatrical text and determining the mechanisms of this intertextuality between texts through fields and classifications agreed upon by the most important critics who wrote and considered intertextuality. Perhaps our previous research (the approach of exposure in the epistemological hallway to intertextuality) was an attempt to interview a terminology, which the researcher intended to monitor, through the mechanisms of intertextuality and other innovative mechanisms, a critical method to read the relational structure of the presentation as it is in the texts, so the new comes in our current (applied) research that it is an experimental attempt Another in the field of (exposure) here to monitor the same relational structure by trying to activate the mechanisms of (exposure), but this time within (the one play with multiple scenes), and here lies the uniqueness of this attempt in the practical process of a critical dramaturgy where the researcher will analyze a single show composed of several scenes according to mechanisms The (reproductive theatrical performances) were attached to exposure after he conducted a (dramatic) experience of the show he chose (as a research sample) to prove the possibility of employing the mechanisms of (exposure) in analyzing (multi-viewing presentation) in the same critical and analytical method that he worked on in his previous research. Perhaps here lies the novelty of this research, according to the researcher's estimation